Three Interventions for Financial Therapy: Fostering an Examination of Financial Behaviors and Beliefs - Rebekah J Nelson; Thomas E Smith; Victoria M Shelton; Kristin V Richards (Journal of Financial Therapy, 2015)
Three interventions that address the emotional components of handling finances are proposed. Drawn from a stepwise model of financial therapy, the three interventions introduced here have the specific aim of incorporating the emotional attributes of traditional financial behaviors and beliefs. First, the Financial Genogram identifies family of origin issues that may affect financial behaviors; second, the Financial Landscape intervention is used when emotional stress occurs in collecting and examining financial documents; and third, the Financial Mirror broadens clients’ perspectives of their financial behaviors. Issues in future research and implementation of the Five Step model are addressed in treating financially distressed clients.
Keywords: Family; finance; financial therapy; five step model; genogram